Associacao de opioides lipofilicos a bupivacaina na anestesia peridural. Ha vantagem no aumento da dose do opioide? - Braz, José Reinaldo Cerqueira [UNESP]; Vanni, S. M D [UNESP]; Menezes, J. A. [UNESP]; Gorayb, S. B S [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP] (My University, 1998)
Background and Objectives: - The effects of associating lipophilic opioids to local anesthetics in epidural anesthesia are not well defined. There are still questions and controversies about opioid doses to be used and their major effects in the epidural block. This study aimed at evaluating the epidural block effects in humans of the association of different fentanyl and sufentanil doses to bupivacaine with 1:200.000 epinephrine. Methods: - A double-blind randomized study was performed in 94 patients of both genders, physical status ASA I, aged between 18 and 60 years, submitted to lower abdomen, perineal or lower limb surgery. Patients without preanesthetic medication were epidurally injected with 100 mg (20 ml) 0.5% bupivacaine, 0.1 mg (0.1 ml) 1%o epinephrine plus a combination of the following drugs: BUPI Group (15 patients): 2 ml of 0.9% saline solution (SS); FENT50 Group (19 patients): 50 μg (1 ml) fentanyl + 1 ml SS; FENT100 Group (20 patients): 100 μg (2 ml) fentanyl; SUF30 Group (20 patients): 30 μg (0.6 ml) sufentanil + SS (1.4 ml); SUF100 Group (20 patients): 50 μg (1 ml) sufentanil + SS (1 ml). The following parameters were studied: onset of sensory block, analgesic block (onset time) in T12, T10 and T8, analgesic block duration in T10 and T12, motor block degree, consciousness degree, need for supplemental perioperative sedation and analgesia, hypotension, bradycardia and peri and post operative side-effects, analgesia duration, proportion of patients needing supplemental analgesia and evaluation of postoperative pain (pain analog visual scale). Results: Groups were demographically uniform. The addition of fentanyl or sufentanil did not alter major characteristics of perioperative epidural block and has not significantly increased postoperative analgesia duration as compared to the use of bupivacaine only. However, the addition of lipophilic opioids has increased the quality of perioperative anesthetic block, translated into a lesser need for supplemental analgesia (p < 0.02). The increased dose of fentanyl and especially of sufentanil has increased the incidence of perioperative drowsiness (p < 0.001) without significant increase in other side effects. Conclusions: In the conditions and doses used, the addition of lipophilic opioids to bupivacaine and the increased dose of lipophilic opioids have improved anesthetic block quality without changes in the epidural block characteristics or a significant increase in side effects, with the exception of drowsiness mainly caused by sufentanil. However, they were not able to provide a significant increase in postoperative analgesia duration.
Association of lipophilic opioids and bupivacaine in epidural anesthesia. Would an increased opioid dose be advantageous?
Keywords: Analgesics, opioids: fentanyl, sufentanil; Anesthetic techniques, regional: epidural; Anesthetics, local: bupivacaine; adrenalin; bupivacaine; fentanyl; local anesthetic agent; opiate; sufentanil; adult; anesthesia induction; bradycardia; clinical trial; consciousness; controlled clinical trial; dose time effect relation; double blind procedure; drowsiness; epidural anesthesia; epidural drug administration; female; human; hypotension; lipophilicity; major clinical study; male; postoperative analgesia; postoperative pain; randomized controlled trial; sedation